1994
DOI: 10.1038/bjc.1994.15
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy-induced alterations in interstitial fluid pressure, volume and water content of an amelanotic melanoma in the hamster

Abstract: Summary The effect of photodynamic therapy (PDT) on interstitial fluid pressure (IFP), tumour volume and water content was measured in melanomas grown in hamsters. Unlike control tumours, treated tumours exhibited a 40-60% increase in volume at 1, 3 and 6 h post PDT. IFP also increased at 1 and 3 h after PDT, but decreased to 50% of control value after 24 h, presumably as a result of PDT-induced microcirculatory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…This study also demonstrates that IFP is elevated in skin melanoma, corroborating previous studies showing elevated IFP in human melanoma (Boucher et al, 1991), human melanoma xenografts in mice (Kristensen et al, 1996;Tufto et al, 1996), and hamster melanomas (Leunig et al, 1992(Leunig et al, , 1994.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study also demonstrates that IFP is elevated in skin melanoma, corroborating previous studies showing elevated IFP in human melanoma (Boucher et al, 1991), human melanoma xenografts in mice (Kristensen et al, 1996;Tufto et al, 1996), and hamster melanomas (Leunig et al, 1992(Leunig et al, , 1994.…”
Section: Discussionsupporting
confidence: 91%
“…Our recent findings revealed decreased neovascularization following intrinsic (NG2 knockout mice) or extrinsic (hydron polymer pellets containing NG2 neutralizing antibody) targeting of NG2 proteoglycan . Lowering tumor IFP by targeting NG2 proteoglycan on pericytes may be a useful approach in improving anticancer drug (conventional chemotherapy) efficacy.This study also demonstrates that IFP is elevated in skin melanoma, corroborating previous studies showing elevated IFP in human melanoma (Boucher et al, 1991), human melanoma xenografts in mice (Kristensen et al, 1996;Tufto et al, 1996), and hamster melanomas (Leunig et al, 1992(Leunig et al, , 1994. …”
supporting
confidence: 91%
“…The wickin-needle technique is invasive and can be used to measure IFP only in superficial tumours. A non-invasive method for measurement of IFP would therefore be useful for predicting the uptake of macromolecules in tumours and hence therapeutic response.Studies of experimental tumours have suggested that the IFP is related to tumour water content in some tumour lines (Lee et al, 1992;Leunig et al, 1994). The proton spin-lattice and spin-spin relaxation times (T1 and T2) of tumour tissue are, to a large extent, (Braunschweiger et al, 1986;Belfi et al, 1991).…”
mentioning
confidence: 99%
“…Studies of experimental tumours have suggested that the IFP is related to tumour water content in some tumour lines (Lee et al, 1992;Leunig et al, 1994). The proton spin-lattice and spin-spin relaxation times (T1 and T2) of tumour tissue are, to a large extent, (Braunschweiger et al, 1986;Belfi et al, 1991).…”
mentioning
confidence: 99%
“…7-11], evaluation of photodynamic therapy [e.g. [12][13][14][15], microcirculation and shock research [16][17][18][19][20][21], studies on mediators of brain edema and damage [e.g. [22][23][24], xenotransplantation and monitoring of transplant patients [e.g.…”
Section: Which Size Should Research Institutes Have?mentioning
confidence: 99%